Calculus: Early Transcendentals 8th Edition

Published by Cengage Learning
ISBN 10: 1285741552
ISBN 13: 978-1-28574-155-0

Chapter 2 - Review - Exercises: 5



Work Step by Step

$$A=\lim\limits_{x\to-3}\frac{x^2-9}{x^2+2x-3}$$ - Consider the numerator: $x^2-9=(x-3)(x+3)$ - Consider the denominator: $x^2+2x-3=(x-1)(x+3)$ Therefore, $$A=\lim\limits_{x\to-3}\frac{(x-3)(x+3)}{(x-1)(x+3)}$$$$A=\lim\limits_{x\to-3}\frac{x-3}{x-1}$$$$A=\frac{-3-3}{-3-1}$$$$A=\frac{3}{2}$$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.